(untitled) (International relations and international law Journal, 2016)
The article analyzes some issues of cooperation in the field of the recognition of qualifications concerning higher education. The article reveals the concept of higher education and the scope of the regional agreements on recognition of qualifications and the practice of recognition of educational qualifications of the Republic of Kazakhstan and the Russian Federation. On the basis of regional agreements and international standards of education were analyzed the concept of “higher education”, the scope of regional agreements for the recognition of higher education qualifications, the possibility of recognition of academic periods and UNESCO’s role in the unification of the rules of international law for the recognition of certificates. According to the analysis, it was revealed that Kazakhstan’s rules of recognition of qualifications do not meet the regional agreement on the recognition of higher education qualifications.